Sosialisasi Teknik Pengelasan di SMK Samudera Indonesia Medan - Jandri Fan HT Saragi; Tambos August Sianturi; Jhon Sufriadi Purba; Goldberd Harmuda Duva Sinaga (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2022)
The purpose of this PkM is to provide welding competency skills to SMK Samudera Indonesia Medan students as a provision to enter the job field or for entrepreneurship for SMK and help the productive process of SMKs that lack funding and practicum facilities. The method used to solve the problems that have been formulated, we need a method that must be followed in order to be able to do a good solution, here is the solution method, namely a survey in SMK to get data for PkM as needed, formulate training materials, make a schedule for the implementation of training related to time, arrange instructors who will provide training, make a design evaluation of activities, The implementation of welding training activities was followed by students. The results of the PkM implementation are as follows: Welding skills that can equip vocational students to enter the world of work are being able to operate a welding machine correctly and be able to connect plates using welding. The responses from vocational students with training assistance from the UHKBPNP Mechanical Engineering Study Program are as follows: they are happy because they have received welding skills which they have not done optimally and the teachers hope that next year they can continue with other programs.